Senescence in Primary Rat Astrocytes Induces Loss of the Mitochondrial Membrane Potential and Alters Mitochondrial Dynamics in Cortical Neurons - Morales-Rosales, Sandra Lizbeth; Santín-Márquez, Roberto; Posadas-Rodriguez, Pedro; Rincon-Heredia, Ruth; Montiel, Teresa; Librado-Osorio, Raúl; Luna-López, Armando; Rivero-Segura, Nadia Alejandra; Torres, Claudio; Cano-Martínez, Agustina; Silva-Palacios, Alejandro; Cortés-Hernández, Paulina; et al. (Frontiers in Aging Neuroscience, 2021)
Decline in brain function during aging is one of the most critical health problems nowadays. Although senescent astrocytes have been found in old age brains and neurodegenerative diseases, their impact on the function of other cerebral cell types is unknown. The aim of this study was to evaluate the effect of senescent astrocytes on neuron mitochondrial function. In order to evaluate neuronal susceptibility to a long and constant SASP exposure, we developed a model using cellular co-cultures in transwell plates. Rat primary cortical astrocytes were seeded in transwell inserts and induced to premature senescence with hydrogen peroxide (stress-induced premature senescent, SIPS). Independently, primary rat cortical neurons were seeded at the bottom of transwells. After neuronal 6 days in vitro (DIV) the inserts with SIPS-astrocytes were placed in the chamber and co-cultured with neurons for six more days. Neuronal viability, redox state (GSH/GSSG), mitochondrial morphology, proteins and membrane potential were determined. Our results showed that neuronal mitochondria functionality was altered after co-culture with senescent astrocytes. In vivo, we found that old animals have diminished mitochondrial OXPHOS proteins, redox state and senescence markers as compared to young rats, suggesting effects of senescent astrocytes as we observed in vitro. Overall, these results indicate that the microenvironment generated by senescent astrocytes can affect neuronal mitochondria and physiology.